Advancing grape breeding through an in vitro embryo germination technique without cold stratification - Zhenhua Liu; Jing Song; Yan Wang; Ailing Yan; Xiaoyue Wang; Huiling Wang; Jiancheng Ren; Haiying Xu; Pingyin Guan; Lei Sun (Horticultural Plant Journal, 2025)
In grape breeding programs, the extensive planting of seedlings is a crucial aspect. However, grape seeds display distinct dormancy traits, necessitating a prolonged cold stratification process for dormancy release. In order to enhance the efficiency of breeding programs, this study presents an innovative in vitro embryo germination technique that eliminates the requirement for cold stratification of seeds. The method involves the disruption of peripheral tissue in grape seed embryos using a straightforward mechanical technique, resulting in the efficient production of a substantial quantity of seed embryos，with a germination rate of up to 88 % for these isolated embryos. These embryos are subsequently cultured in vitro to facilitate germination into seedlings, thereby eliminating the need for cold stratification. Consequently, grape seedlings can be obtained within a significantly reduced timeframe of 30–38 d, expediting the overall grape breeding process. This novel approach not only accelerates grape hybridization but also streamlines the selection of new grape varieties, contributing to an efficient and time-sensitive breeding methodology.